Onderweg met de dialogerende Jezus: Enkele hermeneutische richtlijnen bij het Jezuswoord in Joh 14,6 - Tack, Laura (Tijdschrift voor theologie, 2017)
This article presents an alternative interpretation of the verse, ‘I am the way and the truth and the life. No one comes to the Father except through me.’ (John 14,6) and explains how best to interpret Jesus’s words from the Gospel according to John in the light of Jewish-Christian dialogue. After the author has addressed the potential problems of this verse for the dialogue, she offers a possible solution for the problem of interpretation on the basis of the hermeneutical approach of the normativity of the future (R. Bieringer and M. Elsbernd). The type of interpretation proposed by the author is not merely connected to the three temporal perspectives on the text: a past, a contemporary and a future perspective, but also presents three Christological perspectives on John 14,6. In doing so, this contribution first of all offers an evaluation of the construction of an exclusivist Christ by the earliest Christian community, in order to - secondly - contrast this with the image of the vulnerable Jesus and in third instance, to evoke the image of a Jesus of the dialogue. The author presents these three perspectives on John 14,6 as an invitation to a genuine Christian positioning in the Jewish-Christian dialogue.